2020
DOI: 10.1038/s41586-020-2107-1
|View full text |Cite
|
Sign up to set email alerts
|

Nightside condensation of iron in an ultrahot giant exoplanet

Abstract: Ultra-hot giant exoplanets receive thousands of times Earth’s insolation 1 , 2 . Their high-temperature atmospheres (>2,000 K) are ideal laboratories for studying extreme planetary climates and chemistry 3 – 5 . Daysides are predicted to be cloud-free, dominated by atomic species 6 and substantially hotter than nightsides 5 , 7 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
234
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(261 citation statements)
references
References 64 publications
21
234
1
Order By: Relevance
“…A recent study from Ehrenreich et al (2020) found atomic iron (Fe) in the dayside of the planet WASP-76 b and not in the terminator, concluding that Fe is condensing on the nightside, then falling into deeper layers of the atmosphere. Furthermore, the results in Pluriel et al (2020) and Caldas et al (2019) have investigated how the 3D structure of the atmosphere biases the abundances retrieved with typical retrieval codes, as there is a chemical dichotomy between the day-and nightside that is not considered in a 1D treatment of transit geometry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study from Ehrenreich et al (2020) found atomic iron (Fe) in the dayside of the planet WASP-76 b and not in the terminator, concluding that Fe is condensing on the nightside, then falling into deeper layers of the atmosphere. Furthermore, the results in Pluriel et al (2020) and Caldas et al (2019) have investigated how the 3D structure of the atmosphere biases the abundances retrieved with typical retrieval codes, as there is a chemical dichotomy between the day-and nightside that is not considered in a 1D treatment of transit geometry.…”
Section: Discussionmentioning
confidence: 99%
“…Examining the atmospheres of exoplanets further unveils their planetary properties, with their study made possible by various methods, including transit spectroscopy (e.g., Tinetti et al 2007;Swain et al 2008). Facilities such as the Hubble Space Telescope (HST) and the Spitzer Space Telescope, as well as some ground-based observatories, have provided constraints on these properties for a limited number of targets and, in some cases, have identified the key molecules present in their atmospheres while also detecting the presence of clouds and probing their thermal structure (e.g., Brogi et al 2012;Majeau et al 2012;Stevenson et al 2014;Fu et al 2017;Hoeijmakers et al 2018;Tsiaras et al 2018Tsiaras et al , 2019Pinhas et al 2019;Edwards et al 2020a;Ehrenreich et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These metallicity ranges provide H 2 O abundances which are similar to those recovered here (10 −3 -10 −4 ). The models from Parmentier et al (2018) suggest that, for WASP-121 b, ∼70% of the H 2 O in the 1.4 μm photosphere should be dissociated, compared to~50% in WASP-76 b. Additionally, the metallicity (Fe/H) of WASP-76 is greater than that of WASP-121 and both are above solar, at 0.366 and 0.12 respectively (Ehrenreich et al 2020;Mikal-Evans et al 2019). We could therefore expect WASP-76 b to have slightly more H 2 O than WASP-121 b but, while the bestfit solution agrees with this prediction, the 1σ errors on the abundance are too large to be conclusive.…”
Section: Previous Claims Of Optical Absorbersmentioning
confidence: 99%
“…However, the best-fit inclinations differed between the transit and eclipse light curve and so the orbital parameters were set to values from Ehrenreich et al (2020). The limb-darkening coefficients were selected from the best available stellar parameters using values from Claret et al (2012Claret et al ( , 2013 and using the stellar parameters from Ehrenreich et al (2020). We did not fit for the limb-darkening coefficients, as they are degenerate with other parameters, particularly given the periodic gaps in the HST data.…”
Section: Data Reductionmentioning
confidence: 99%
See 1 more Smart Citation